2020
DOI: 10.31186/jspi.id.15.2.195-199
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Populasi dan Performans Reproduski Ternak Babi di Kabupaten Sumba Timur

Abstract: This study aimed to determine the population structure and reproduction performance of pigs in East Sumba Regency. The study was conducted from February to May 2017 with the research method used is a survey with direct interviews of 200 respondents. Data were analyzed by descriptive statistical approach which is depicted in the frequency table of each indicator. The measured variables were male and female population structure covering children (0-3 months), young (3-7 months), adults (>8 months). While reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Inseminasi buatan (IB) dilaporkan mampu meningkatkan populasi karena memiliki angka melahirkan anak (farrowing rate) setelah aplikasi IB yang diamati dari pertama kali induk bunting mampu melahirkan anak dengan kisaran litter size 10 sampai 11 anak (Sobczynska et al, 2013;Soltesz et al, 2013. ), dan berkisar antara 12-14 ekor pada kelahiran ke dua yang dilaporkan oleh Gobai et al, (2013) sedangkan litter size babi yang dikawinkan secara alamiah rata-rata 9 ekor (Wea, 2009); rataan liter size diperoleh dalam penelitian oleh Kaka et al, (2020) mencapai 9,75 ekor; dan rata litter size 8,70 ekor. Anak babi lahir hidup hasil inseminasi buatan (IB) dilaporkan lebih tinggi 24 % dari perkawinan secara alami (Adegbeye, 2020).…”
Section: Peran Inseminasi Buatan (Ib) Dalam Meningkatkan Populasi Ter...unclassified
“…Inseminasi buatan (IB) dilaporkan mampu meningkatkan populasi karena memiliki angka melahirkan anak (farrowing rate) setelah aplikasi IB yang diamati dari pertama kali induk bunting mampu melahirkan anak dengan kisaran litter size 10 sampai 11 anak (Sobczynska et al, 2013;Soltesz et al, 2013. ), dan berkisar antara 12-14 ekor pada kelahiran ke dua yang dilaporkan oleh Gobai et al, (2013) sedangkan litter size babi yang dikawinkan secara alamiah rata-rata 9 ekor (Wea, 2009); rataan liter size diperoleh dalam penelitian oleh Kaka et al, (2020) mencapai 9,75 ekor; dan rata litter size 8,70 ekor. Anak babi lahir hidup hasil inseminasi buatan (IB) dilaporkan lebih tinggi 24 % dari perkawinan secara alami (Adegbeye, 2020).…”
Section: Peran Inseminasi Buatan (Ib) Dalam Meningkatkan Populasi Ter...unclassified
“…Based on the description above, this study aims at measuring the profitability of three types of pig farming in Indonesia, namely farrow-to-finish, pig-finishing, and pig nursery. Previous studies on the profitability of pig farming were based on primary data and in the form of case studies in certain areas (Iyai et al, 2013;Soewandi et al, 2013;Sarajar et al, 2019;Kaka et al, 2020) and have not been observed the type is pig farming run by the farmers. There is only Kusumastuti and Irham"s research (2001) discussing the three different types of pig farming but limited only on a small sample and particular region (Sleman).…”
Section: Introductionmentioning
confidence: 99%